The use of ractopamine as a feed additive: A review - Shams, Gamal A.; Ibrahim, Hosny A.; Mohammed, Nagah E.; Hassan, Heba M.; Semary, Nashwa S. (Journal of Advanced Veterinary Research, 2024)
Ractopamine hydrochloride is a Î²-adrenergic agonist that increases growth, feed efficiency, and fat deposition. Because of its ability to increase muscling, average daily gain, efficiency, and carcass weight, ractopamine hydrochloride has been used as a feed additive growth enhancer. Ractopamine is also a member of the phenylethanolamine class of chemicals, which is used as a feed supplement in meat-producing animals. This review threw the light on the use of ractopamine to improve weight gain and as a feed addition. Furthermore, the potential negative health effects of ractopamine were explored.